TRAILS AND UPLIFTMENT OF BROKEN WINGS : A COMPARATIVE READING OF AMULYA MALLADI’S THE SOUND OF LANGUAGE AND A HOUSE FOR HAPPY MOTHERS - Shalini K.J; P. Premalatha; Chrissie Gracelyn David (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian English Writers capture the changing moods of the Indian society and Amulya Malladi serves as a best example in portraying them. She has contributed immensely to bring out the sufferings of the people belonging to the Indian society. Her novel TheSound of Language (2008) portrays the problems faced by the refugees all over the world generally and the sufferings of the settlers of Denmark in particular. The characters taken for analysis are Raihana, Layla and Christina. The novel A House for Happy Mothers (2016) portrays about the realistic journey faced by the women undergoing surrogacy in a strictly traditional society and their hidden heart-wrenching emotions. The novel briefly describes the confusing mentality of a childless woman named Priya. The paper portrays the universal trails faced by women and how they struggle hard for their own upliftment and the upliftment of their family members. The paper highlights that individuals are themselves responsible for their own pitiable plight and personal upliftment plays a major role in one’s development instead of the external upliftment rendered to them by the society or the family members.